2022
DOI: 10.3390/antiox11010174
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light-Triggered Generation of Reactive Oxygen Species and Induction of Local Hyperthermia from Indocyanine Green Encapsulated Mesoporous Silica-Coated Graphene Oxide for Colorectal Cancer Therapy

Abstract: Near-infrared (NIR) light-mediated photothermal therapy (PTT) and photodynamic therapy (PDT) have widely been used for cancer treatment applications. However, a number of limitations (e.g., low NIR absorption capacity of photothermal agents, insufficient loading efficiency of photosensitive molecules) have hindered the widespread use of NIR-mediated cancer therapy. Therefore, we developed a mesoporous silica-coated reduced graphene oxide (rGO) nanocomposite that could provide a high encapsulation rate of indoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Furthermore, we conducted a live/dead assay to visualize the therapeutic efficacy of the melanoma cells via the NIR laser irradiation and nanocomposites ( Figure 7 B). In the control group, although a 808 nm NIR laser was irradiated to the B16F10 cells, a number of cells exhibited the green fluorescence, suggesting that only the NIR laser irradiation did not affect the cell viability [ 58 ]. In the B16F10 cells treated with the ID@MOS-Fc-CDHA nanocomposites without the NIR laser irradiation, some sporadic red fluorescence was observed, due to the chemo-therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we conducted a live/dead assay to visualize the therapeutic efficacy of the melanoma cells via the NIR laser irradiation and nanocomposites ( Figure 7 B). In the control group, although a 808 nm NIR laser was irradiated to the B16F10 cells, a number of cells exhibited the green fluorescence, suggesting that only the NIR laser irradiation did not affect the cell viability [ 58 ]. In the B16F10 cells treated with the ID@MOS-Fc-CDHA nanocomposites without the NIR laser irradiation, some sporadic red fluorescence was observed, due to the chemo-therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of tumor suppression can be explained by the synergistic effects of PTT from rGO and PDT from ICG. The experiments are performed using an 808 nm laser with 1 W/cm 2 for 10 min [ 97 ]. Irrespective of this progress, fluorescence-based techniques are still limited to the laboratory stage presumably due to the limitations of poor resolution, and because the drug molecules should be fluorescent.…”
Section: Graphene Nanocomposite Theranostics For Multimodal Imaging G...mentioning
confidence: 99%
“…Choi et al, Yang et al, Mirrahimi et al, Hong et al, Jia et al, Yang et al, Belu et al, and Lim et al demonstrated multimodal imaging (CLSM, MRI, CT, PET, PAI, RAMAN and ToF-SIMS) and multimodal therapies including chemo, gene, and PTs. Most of these researchers have also given tremendous efforts to improve the therapeutic capabilities by minimizing GNCs concentration, laser wavelengths from the first biological windows to the second biological window, and less laser powers and irradiation times [ 84 , 97 , 107 , 108 , 119 , 120 , 132 , 139 , 145 , 146 ]. Keshav et al, provided excellent pharmacokinetic data to take the material towards preclinical trials.…”
Section: Graphene Nanocomposite Theranostics For Multimodal Imaging G...mentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions, ROS can be effectively neutralized by the enzymes superoxide dismutase, catalase, glutathione, and thioredoxin to control the equilibrium oxidation-reduction (redox) state. However, when redox homeostasis is destroyed or relieved, changes in ROS levels will lead to physiological and pathological changes (61,62). In addition, ROS play a positive role in regulating intracellular signal transduction pathways, with numerous biological conduits being constrained by a variety of ROS species, which are the key to maintaining cellular homeostasis.…”
Section: Reactive Oxygen Species (Ros)-responsive Npsmentioning
confidence: 99%